The Use of Succinylcholine in Brugada Syndrome: A Case Report and Discussion of Literature - Marcus M. de Wolf; Nellie M. Rus; Guus H. Beljaars; Hanno L. Tan (Case Reports in Anesthesiology)
We describe a patient with a major depression and a newly discovered Brugada syndrome, who was successfully treated with 35 electroconvulsive therapy sessions using succinylcholine as muscle relaxant. We discuss the use of succinylcholine in patients with Brugada syndrome.